The Effectiveness of the Accountants in Curtailing Financial Corruption in the South-South and South-East Public Sector of Nigeria - Osagioduwa, Lucky Ogbomo; Atube, Elizabeth N. (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
This study investigated the effectiveness of accountants in curtailing financial corruption in the south-south and southeast public sectors of Nigeria. The study was carried out in Edo, Delta, Enugu, and Anambra States respectively. Primary data were obtained through a structured questionnaire. A survey design was employed in the study. A convenient Sampling Technique was employed in selecting respondents in the four states’ public organizations. A total of one hundred and sixty-two (162) respondents were sampled. Descriptive statistical techniques such as, charts, mean, standard deviation, tables, and percentages response analysis were used for data description. Cronbach alpha coefficient was used to test for the reliability of the research instrument and the result was. The Pearson Product Moment Correlation Coefficient (PPMCC) and the Chi-square Techniques were employed in testing the hypotheses. The results revealed that accountants helped in fighting corruption in the public sector of Nigeria and the engagement of more professional accountants will help in curtailing financial corruption in the public sector of Nigeria. The study, therefore, concludes that accountants are effective in combating financial corruption in the South-South and South-East public sectors of Nigeria within their scope of engagement despite severe threats from management. It was recommended that study leave, job security, regular training, and study grants should be made available to the accountants among others.